Dispersion de Ralstonia solanacearum en suelos cultivados con platano en el Piedemonte Llanero - Tapiero, A.L.=700 1 Morales, A.; Rodriguez, S.M.
(Es, En)
Ilus., 24 ref.
Keywords: MUSACEAE; PLATANO; ENFERMEDADES DE LAS PLANTAS; DISTRIBUCION GEOGRAFICA; PATOGENICIDAD; COLOMBIA; RALSTONIA SOLANACEARUM; ENFERMEDAD DEL MOKO; REVISTA CORPOICA